Intelligent search system for resume and labor law - Nguyen, Hien (2024)
The data and code are available at figshare: Nguyen, Hien (2023). Dataset for Intelligent Searching System on Resumes and Legal documents. figshare. Dataset. https://doi.org/10.6084/m9.figshare.24818709.v1.